SPIRITUALITAS DAN LANDASAN SPIRITUAL (MODERN AND ISLAMIC VALUES); DEFINISI DAN RELASINYA DENGAN KEPEMIMPINAN PENDIDIKAN - Faizah, Kurniyatul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Spirituality is not something foreign to humans, because it is the core (core) of humanity itself. Manpu's spiritual drive brings the material dimension of man to his spiritual dimension (spirit, divinity) by understanding and internalizing His attributes, living life according to His instructions and imitating His Messenger. The goal is to gain His pleasure, to become a